2017
DOI: 10.12681/jhvms.15442
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing HACCP implementation in the food industry

Abstract: HACCP application in food processing plants could improve food safety and lead to a reduction of food-borne diseases. Apparent lack of HACCP implementation in several food businesses may be due to presence of various technical barriers. The aim of this review is to explore the lists of motives and barriers to implementation of the HACCP system as outlined in the published literature and to evaluate respective impact. Lack of awareness of HACCP, no perceived benefits, lack of training, management regressions, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
0
7
0
4
Order By: Relevance
“…Визначення показників санітарномікробіологічного контролю холодильних камер, об'єктів на потужностях з виробництва та обігу є актуальним, тому що це запобігає негативному впливу на безпечність та якість м'яса забійних тварин в терміни закінчення його зберігання та відвертає нанесення шкоди здоров'ю пересічного споживача і дає можливість профілактувати харчові отруєння та харчові токсикоінфекції (Milios et al, 2012).…”
Section: вступunclassified
“…Визначення показників санітарномікробіологічного контролю холодильних камер, об'єктів на потужностях з виробництва та обігу є актуальним, тому що це запобігає негативному впливу на безпечність та якість м'яса забійних тварин в терміни закінчення його зберігання та відвертає нанесення шкоди здоров'ю пересічного споживача і дає можливість профілактувати харчові отруєння та харчові токсикоінфекції (Milios et al, 2012).…”
Section: вступunclassified
“…The HACCP aims to monitoring the entire production flow in order to achieve a safe product according to the applicable standards [ 12 ]. The benefit of implementing this food safety management system is both the achievement of higher quality products and the reduction of disease transmission through food [ 13 ]. Altemimi and other entities analyzed the level of microbial contamination of various types of surfaces in contact with food, as well as the effectiveness of disinfectants on contaminated surfaces, concluding that the application of HACCP principles in Iraq improved food quality [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The managers of food businesses need to be aware that the application of HACCP rules leads to increased performance of production processes, reduced losses and therefore lower costs. The improvements of customer relationships, as well as an increase in the customer portfolio and the firm's prestige are the benefits of running the company's business according to HACCP rules [ 13 ]. Analyzing the impact of HACCP on the Jamaican hotel industry, Fletcher, Maharaj and James [ 19 ] concluded that the compliance with food standards is reflected in the appreciation given by tourists, but also that the implementation of the standards requires specific policies tailored to different types of hotels.…”
Section: Introductionmentioning
confidence: 99%
“…There is an unequivocal need to increase new knowledge at managerial level in fish processing. One of the key factors influencing the successful implementation of the HACCP system is the lack of staff training, in addition to the commitment of the management for the implementation of the HACCP system and the implementation costs, found out Milios et al (2017) in the research carried out in Greece. On the other hand, adequate training and experience that the members of the HACCP team have in the field of food safety ensure an effective implementation of the procedures of the HACCP system, reduce the number of product recalls and increase the reputation of the company according to this authors.…”
Section: Introductionmentioning
confidence: 99%